Iconographic Studies Poster of the Exhibition and Night Market of the Dutch East Indies and Europe, 1930s Colonial Period - Baskoro Suryo Banindro; Listia Natadjaja; Nina Hansopaheluwakan Edward (Paramita: Historical Studies Journal, 2025)
Abstract: This study analyses Art Deco (1930s) colonial exhibition posters from the Dutch East Indies and Europe to uncover their active role as an instrument of visual hegemony that transcends the discourse of exoticism. Through a critical comparative iconography approach (Panofsky's adaptation) reinforced by postcolonial theory (Said, 1978) and representation (Hall), the research reveals how Art Deco syntax, rigid geometry, machine typography, and modern chromaticism are used to transform colonial violence into "modernity", domesticating alterity through linguistic distortion. Build a global myth about the world order under European leadership. Key findings point to different aesthetic strategies: while European (French/Belgian) posters erase indigenous traces, the Dutch East Indies version adopts local terms distortively to assert epistemic control. The two met in Art Deco's function as a "universal visual language" that naturalized colonial hierarchies. Research concludes that Art Deco is not just a decorative style, but an ideological weapon that transforms exploitation into aesthetics, and oppression into "progress" in the global imagination of the 1930s. This underlines the enduring power of visual culture to shape ideologies, highlighting how the Art Deco movement functioned as an active agent in the legitimation and perpetuation of colonial dominance. Abstrak: Penelitian ini menganalisis poster pameran kolonial bergaya Art Deco (1930-an) dari Hindia Belanda dan Eropa untuk membongkar peran aktifnya sebagai instrumen hegemoni visual yang melampaui wacana eksotisme. Melalui pendekatan ikonografi komparatif kritis (adaptasi Panofsky) yang diperkuat teori poskolonial (Said) dan representasi (Hall), penelitian mengungkap bagaimana sintaksis Art Deco, geometri rigid, tipografi mesin, dan kromatik modern, dimanfaatkan untuk mengubah kekerasan kolonial menjadi "modernitas", mendomestikasi alteritas melalui distorsi linguistic. Membangun mitos global tentang tatanan dunia di bawah kepemimpinan Eropa. Temuan kunci menunjukkan perbedaan strategi estetik: sementara poster Eropa (Prancis/Belgia) menghapus jejak pribumi, versi Hindia Belanda mengadopsi istilah lokal secara distorsif untuk menegaskan kontrol epistemik. Keduanya bertemu dalam fungsi Art Deco sebagai "bahasa visual universal" yang menaturalisasi hierarki kolonial. Penelitian menyimpulkan bahwa Art Deco bukan sekadar gaya dekoratif, melainkan senjata ideologis yang mentransformasi eksploitasi menjadi estetika, dan penindasan menjadi "kemajuan" dalam imajinasi global era 1930-an.